Multipoint Observations of Magnetosheath Response to Foreshock Transients. Issue 2 (17th February 2020) - Cai, Chunlin; Wei, Xinhua
Abstract: Multispacecraft observations of the magnetosheath responses to various foreshock transients in a single event on 17 March 2004 are reported in this paper. The Cluster spacecraft recorded long‐standing large amplitude ULF waves with both compressive and transverse components in the magnetosheath. Additionally, two transient structures with depressions in density and magnetic field were observed in this period. One structure contains greatly heated and significantly deflected plasmas in the middle and a cold solar wind population at its trailing edge, which is identified as a spontaneous hot flow anomaly with a remnant of the foreshock caviton. It is transmitted through the magneosheath and evolved into a magnetosheath cavity. This cavity was subsequently encountered by the Double Star TC‐1 spacecraft deeper inside the magnetosheath. Meantime, fluxes of hot ions in the energy range of 5–38 keV exhibit quasiperiodic variations. These energetic ions are earthward with pitch angle distributions of alternately field aligned or antifield aligned. A correlation between its flux variations and the transverse fluctuations of the ULF waves is found. Moreover, magnetosheath filamentary structures with a series of anticorrelated oscillations of density and temperature were observed simultaneously. Key Points: Magnetosheath responses to various foreshock transients in a single event are examined A magnetosheath cavity evolves from a spontaneous hot flow anomaly Energetic ion injections and the related magnetosheath filamentary structures were observed simultaneously